Cognitive Control and Flexibility as Predictor of Career Adaptability in Emerging Adults - DEMİRTAŞ, Ayşe Sibel; KARA, Ahmet (Kastamonu Egitim Dergisi, 2022)
Purpose: The main purpose of this study is to reveal the predictive role of cognitive control and flexibility on career adaptabilityof emerging adults and the relationships among the variables.Design/Methodology/Approach: A total of 318 emerging adults, 193 female (60.7%) and 125 male (39.3%) participated in thestudy. The age range of the participants in the study is 19-26 and the mean age is 21.52 (SD: 1.57). The data of the study werecollected by the Career Adaptability Scale and the Cognitive Control/Flexibility Questionnaire. Pearson correlation coefficientand multiple regression analysis were used to analyze the data.Findings: The findings of the study revealed that the variables in the study showed positive correlations and appraisal/copingflexibility factor significantly predicted career adaptability. According to the regression model, appraisal/coping flexibility factorexplains approximately 12% of the total variance in career adaptability.Highlights: The results of the study were discussed in light of the literature, and the recommendations were proposed to theexperts and researchers working in the field of career psychological counseling.